PENGARUH UPAH, MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PT. BALINA AGUNG PERKASA CILEUNGSI - Thadeus Taa; Freddrick Tiagita Putra (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
Purpose the determining factors in improving performance is how the wages are given and the work culture that is able to motivate employees for high performance. This study aims to determine the effect of wages, motivation and work culture on the performance of employees at PT. Balina Agung Perkasa Cileungsi either partially or simultaneously. The method used in this research is explanatory research with quantitative research type and the data source used is primary data in the form of questionnaires. The population in this study were employees of PT. Balina Agung Perkasa Cileungsi while the sampling technique in this study used a non-probability sampling method with data collection techniques using a purposive sampling approach by setting certain criteria so that a sample of respondents was obtained. The results showed that either partially or simultaneously, work motivation and work culture had a significant effect on the performance of PT. Balina Agung Perkasa Cileungsi.